Trend of home or hospital delivery and child birth among Muslim women of Biratnagar, Nepal (Health Renaissance, 2017)
Background: Maternal morbidity and mortality remains one of the biggest public health challenges in Nepal. This paper explores the trend of home or hospital delivery and child birth in certain ethnic group. The illiteracy women’s low socio economic status in the society, lack of access and difficult geographical rugged terrain are major reasons for not delivering children in health institutions in Nepal.Objective: To find out the trend of hospital or home delivery among Muslim women of Biratnagar city.Methods: Cross-sectional study was conducted among 200 Muslim women of ward 7 of Biratnagar municipality. They were interviewed to assess their health seeking trend of home or hospital delivery and child birth along with factors associated with the use of health services. Information's on usages of health services, education level, family structure, and occupational status information were also collected using a pre-tested and structured questionnaire.Results: The overall institutional delivery in the study population was 24.5%. Illiteracy, low socio-economic status, and poverty in women are the major challenging features of not delivering babies in health institutions.Conclusion: Only one fourth of the women of the study population had hospital/health institutional delivery. Hospital deliveries were seen among the educated women with many antenatal visits. Therefore female education must be encouraged in this community. Health Renaissance 2015;13 (1): 68-76